Complementary Chemical Vapor Deposition Fabrication for Large‐Area Uniform Graphene Glass Fiber Fabric. Issue 7 (24th May 2022) - Liu, Ruojuan; Yuan, Hao; Li, Junliang; Huang, Kewen; Wang, Kun; Cheng, Yi; Cheng, Shuting; Li, Wenjuan; Jiang, Jun; Tu, Ce; Qi, Yue; Liu, Zhongfan
Abstract: The lightweight, flexible, high‐performance electrothermal material is in high demand in object thermal management. Graphene glass fiber fabric (GGFF) is characterized by excellent electrical conductivity, light weight, and high flexibility, showing superiorities as an electrothermal material. However, the traditional single‐carbon‐precursor chemical vapor deposition (CVD) graphene growth strategy commonly suffers from the severe thickness nonuniformity of the large‐sized graphene film along the gas‐flowing direction. Herein, a complementary CVD graphene growth strategy based on the simultaneous introduction of high‐ and low‐decomposition‐energy‐barrier mixed carbon precursors is developed. In this way, the large‐area uniform GGFF with a dramatically decreased nonuniformity coefficient is fabricated (0.260 in 40 cm × 4 cm). GGFF‐based heater presents a widely tunable temperature range (20–170 °C) at low working voltage (<10 V) and uniform large‐area heating temperature (171.4 ± 3.6 °C in 20 cm × 15 cm), which realizes remarkable anti/deicing performances under the low energy consumption (fast ice melting rate of 79 s mm −1 under a low energy consumption of 0.066 kWh mm −1 m −2 ). The large‐area uniform GGFF possesses substantial advantages for applications in thermal management, and the complementary CVD fabrication strategy shows reliable scalability and universality, which can be extended to the synthesis of various materials. Abstract : A complementary chemical vapor deposition strategy is designed, enabling the large‐area uniform fabrication of graphene glass fiber fabric in a wide range of sheet resistance. Notably, the obtained graphene glass fiber fabric presents impressive electrothermal performances in a wide temperature range at low‐level working voltages, ultrafast electrothermal response, and uniform heating temperature, which realize the remarkable anti/deicing performances under low energy consumption.